DINÂMICA E ESTRATÉGIAS DE DESENVOLVIMENTO AGRÍCOLA DO MUNICÍPIO DE PANAMBI – RS - Jezewski, Tiago J.; Wenningkamp, Douglas; Basso, Nilvo; Henriques, Angélica d. O. (Salão do Conhecimento, 2013)
Resumo